Os efeitos das mudanças climáticas nos fluxos migratórios: refugiados ambientais e o reconhecimento de seu status jurídico como garantia à dignidade da pessoa humana - Monteiro, Andercley da Silva (2023)
The present work aims to analyze the consequences of climate change on migratory flows, specifically with regard to environmental refugees and the adequacy and efficiency of current international instruments to protect and guarantee the dignity of the human person in this group. In this context, two central hypotheses drive this study: climate change alters migratory flows, resulting in the emergence of environmental refugees and the insufficiency of the standards currently in force to meet the complexity of the problem faced by the global environmental crisis. To this end, a brief historical and conceptual review is proposed regarding climate change, environmental degradation, migratory flows and the related global context, demonstrating, furthermore, the poignant need to find shared solutions to protect those who find themselves in a condition of environmental refugees. A qualitative research using an inductive method is then carried out, the source of bibliographical research, the techniques of the referent, the category, the operational concept and the record. Thus, it appears that climate change constitutes a preponderant factor in the alteration of migratory flows, culminating in the emergence of environmental refugees who, given the gap in the current international normative system, lack specific protection, which highlights the need for renewal in international hermeneutics, in order to consider the dignity of the human person as an irreplaceable element of protection through the conception of shared responsibilities and international solidarity between Nations.